NILAI-NILAI EDUKATIF PADA CERITA RAKYAT KI AGENG PANDANARAN: KAJIAN SOSIOLOGI SASTRA - Lestari, Sri; Nabilah, Nabilah (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to analyze the educational values in the folklore of Ki Ageng Pandanaran using the sociological approach to literature. The research is conducted to describe the phenomena occurring in the Paseban community in Bayat, Klaten Regency, Central Java Province, Indonesia, through educational values examined via the sociological approach to literature. This study employs a qualitative descriptive method, where the data, categorized from observations, documentation, and interviews, are analyzed and conclusions are drawn. Furthermore, the focus of this study is the folklore of Ki Ageng Pandanaran, particularly its educational values. The data in this study consist of folklore documents and interview results, which are then analyzed using the sociological approach to literature. The research findings include religious educational values, moral educational values, historical educational values, and heroic educational values. The analysis concludes that the educational values in the folklore of Ki Ageng Pandanaran can provide examples and knowledge for daily life. The societal relationships depicted reflect a harmonious, peaceful existence that upholds the teachings of Ki Ageng Pandanaran. The study of educational values in the folklore of Ki Ageng Pandanaran can be related to social disparities to foster social awareness within the community.